Time-scale dynamics of proteome and transcriptome of the white-rot fungus Phlebia radiata: growth on spruce wood and decay effect on lignocellulose - Kuuskeri, Jaana (Biotechnol Biofuels, 2016)
BACKGROUND: The white-rot Agaricomycetes species Phlebia radiata is an efficient wood-decaying fungus degrading all wood components, including cellulose, hemicellulose, and lignin. We cultivated P. radiata in solid state cultures on spruce wood, and extended the experiment to 6 weeks to gain more knowledge on the time-scale dynamics of protein expression upon growth and wood decay. Total proteome and transcriptome of P. radiata were analyzed by peptide LC–MS/MS and RNA sequencing at specific time points to study the enzymatic machinery on the fungus’ natural growth substrate. RESULTS: According to proteomics analyses, several CAZy oxidoreductase class-II peroxidases with glyoxal and alcohol oxidases were the most abundant proteins produced on wood together with enzymes important for cellulose utilization, such as GH7 and GH6 cellobiohydrolases. Transcriptome additionally displayed expression of multiple AA9 lytic polysaccharide monooxygenases indicative of oxidative cleavage of wood carbohydrate polymers. Large differences were observed for individual protein quantities at specific time points, with a tendency of enhanced production of specific peroxidases on the first 2 weeks of growth on wood. Among the 10 class-II peroxidases, new MnP1-long, characterized MnP2-long and LiP3 were produced in high protein abundances, while LiP2 and LiP1 were upregulated at highest level as transcripts on wood together with the oxidases and one acetyl xylan esterase, implying their necessity as primary enzymes to function against coniferous wood lignin to gain carbohydrate accessibility and fungal growth. Majority of the CAZy encoding transcripts upregulated on spruce wood represented activities against plant cell wall and were identified in the proteome, comprising main activities of white-rot decay. CONCLUSIONS: Our data indicate significant changes in carbohydrate-active enzyme expression during the six-week surveillance of P. radiata growing on wood. Response to wood substrate is seen already during the first weeks. The immediate oxidative enzyme action on lignin and wood cell walls is supported by detected lignin substructure sidechain cleavages, release of phenolic units, and visual changes in xylem cell wall ultrastructure. This study contributes to increasing knowledge on fungal genetics and lignocellulose bioconversion pathways, allowing us to head for systems biology, development of biofuel production, and industrial applications on plant biomass utilizing wood-decay fungi. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-016-0608-9) contains supplementary material, which is available to authorized users.